Forty Years of Clathrin‐coated Vesicles. (6th November 2015) - Robinson, Margaret S.
Abstract : Forty years ago, Barbara Pearse purified coated vesicles from pig brain and discovered the protein clathrin. This review highlights some of the key discoveries that have been made in the intervening years, and how they have shaped our way of thinking, not only about clathrin‐coated vesicles, but about intracellular transport in general. Abstract : The purification of coated vesicles and the discovery of clathrin by Barbara Pearse in 1975 was a landmark in cell biology. Over the past 40 years, work from many labs has uncovered the molecular details of clathrin and its associated proteins, including how they assemble into a coated vesicle and how they select cargo. Unexpected connections have been found with signalling, development, neuronal transmission, infection, immunity and genetic disorders. But there are still a number of unanswered questions, including how clathrin‐mediated trafficking is regulated and how the machinery evolved.